Manchester, capital of the nineteenth century. (February 2013) - Wolff, Janet
This essay accepts David Frisby's invitation to take seriously the method of sociological impressionism employed by Georg Simmel, and the related strategies of Walter Benjamin (sequences of quotations, selection of key aspects of modernity – dialectical images). To that end, it proposes Manchester, instead of Paris, as the 'capital of the nineteenth century', through the presentation of examples of its paradigmatic figures and events: the 1857 exhibition, the collector and the art dealer, the discovery of a synthetic colour, a certain historic desk, and the warehouse and the mill. Through this writing strategy, the 'fragments of modernity' take on a rather different aspect.